Students’ need satisfaction and frustration profiles: Differences in outcomes in physical education and physical activity-related variables. - Burgueño Menjibar, Rafael; García-González, Luis; Abós, Ángel; Sevil-Serrano, Javier (Sage, 2023)
Grounded in self–determination theory, the objectives of the present research were to identify latent profiles based on need-based experiences in physical education (PE), and to examine differences in outcomes in PE (i.e. motivation, experiences, and oppositional defiance) and physical activity-related variables outside of PE (i.e. physical activity intention, moderate–to–vigorous physical activity, and meeting physical activity recommendations) across the identified profiles. A purposive sample of 1062 secondary PE students (526 boys and 536 girls; Mage=14.15, SD=1.51) participated in this cross sectional study. Results from latent profile analysis revealed four need satisfaction and frustration profiles: “high need satisfaction–low need frustration”; “moderate need satisfaction–low need frustration”; “moderate need satisfaction–moderate need frustration”; and “low need satisfaction–high need frustration”. For outcomes in PE, the “high need satisfaction–low need frustration” profile was the most adaptive, while the “low need satisfaction–high need frustration” profile obtained the most maladaptive pattern of outcomes. The “moderate need satisfaction–low need frustration” profile was more adaptive than “moderate need satisfaction–moderate need frustration” profile, although both were similar in experiences and oppositional defiance. For physical activity-related outcomes outside of PE, the “high need satisfaction–low need frustration” profile scored highest, while no differences were obtained among the three remaining profiles. These results provide further insight into the importance for PE teachers not only to support students’ need satisfaction, but also to minimize need frustration, in obtaining the most optimal pattern of outcomes in PE, as well as a more active lifestyle among students
https://openpolicyfinder.jisc.ac.uk/id/publication/9143?from=single_hit
Keywords: Educación física - Estudio y enseñanza; Investigación activa en educación; Autonomy; Competence; Relatedness; Behavioral regulation; Physical activity